Seroprevalence of Hepatitis A in Patients with Chronic Hepatitis C in Isfahan Province - Shoaei, Parisa (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVES: Patients with Hepatitis C Virus infection are at high risk of getting hepatitis A virus. Hepatitis A virus is an important widespread virus that usually causes more severe medical consequences in patients with chronic liver disease. The purpose of this study was to evaluate prevalence of Hepatitis A Virus antibody in patients with chronic HCV in Isfahan province, Iran. METHODS: A cross-sectional study was carried out on 117 patients with chronic hepatitis C virus from spring 2010 to spring 2011. Subject's characteristics such as age, gender, education, genotype of HCV infection and history of intravenous drug use were collected by questionnaire and studied. Statistical analysis was done by SPSS software (version 19.0. 2010, SPSS) using Chi-square test, Fisher Exact tests and Cochran-Armitage trend test. RESULTS: The mean age of the subjects was 33.18 ± 10.97 years. The seroprevalence of HAV was 94.9% in patients with chronic HCV. The prevalence of anti-HAV increased nearly as age increased. But, there was no statistically significant difference in HAV positive rate according to the age groups (P = 0.242) and other patient's characteristics. CONCLUSIONS: According to the high HAV immunity in our study and less severe form of HAV infection, vaccination was not required in these patients. However, hepatitis A vaccination program should be performed in HAV seronegative patients with HCV to produce an adequate immune response.